P034 A dietary fibre intervention shapes the microbiome towards an anti-inflammatory tone. (25th January 2019) - Reider, S J; Moosmang, S; Tragust, J; Trgovec-Greif, L; Tragust, S; Przysiecki, N; Sturm, S; Tilg, H; Rattei, T; Stuppner, H; Moschen, A R
Abstract: Background: The intestinal microbiome in IBD shows characteristic changes already early in the course of disease. These include enrichment of Proteobacteria and reduction of short chain fatty acid (SCFA) producing Lachnospiraceae . Prebiotics are one way to modulate a dysbiotic microbiome but insight into the interactions between diet, microbiome and host remains limited. This study aims to decipher novel links between a dietary fibre intervention with partially hydrolysed guar gum (PHGG) and structural and metabolic changes of the microbiome, investigating the potential of dietary fibre in IBD prevention and supportive treatment. Methods: A clinical trial including 19 healthy volunteers (8 males, 11 females) was performed. Stool, serum and urine samples were collected weekly for 9 weeks allowing every study participant to serve as their own control. The study included 3 periods: a 3-week baseline, a 3-week intervention, and a 3-week washout phase. During the intervention phase, participants received daily dosing of 5 g PHGG for 3 days followed by 10 g PHGG for 4 days in the first week, proceeding with 2 weeks of 15 g PHGG per day. A medical and nutritional history was taken for every participant at baseline, questionnaires on abdominal symptoms were completed weekly and stool habits were recorded daily using the Bristol Stool Chart. Microbiome structure was assessed by 16S metagenomics using both V1-V3 and V3-V4 regions and Tax4Fun was used to estimate functional profiles from taxa abundance. Faecal metabolomics were studied by nuclear magnetic resonance spectroscopy (NMR). Metagenomic and metabolomic data were linked using sparse regression matrices and analysis of co-occurrence/-exclusion. Results: PHGG increased stool frequency and reduced stool consistency. This laxative effect was more pronounced in males than females and persisted during the washout phase. PHGG decreased α diversity during intervention, but this effect did not persist. Β-diversity was not different between study periods but taxa changing significantly under PHGG treatment were detected: PHGG was associated with reduction in certain Erysipelotrichaceae and Pasteurellaceae and increase in certain Lachnospiraceae . Principal component analysis of NMR spectra showed significant gender-specific differences and numerous significantly changed metabolites before, during and after intervention were detected. Conclusions: This study shows that a dietary intervention with PHGG induces beneficial changes of intestinal microbial composition and function along with changes in microbiota-derived metabolites. PHGG supplementation could be one way to attenuate IBD associated changes of the microbiome. We plan to investigate these effects by additional experiments in models of intestinal inflammation.